Extraosseous osteosarcoma: A case report and review of the literature - Apiruk Sangsin (2018)
Extraosseous osteosarcoma (EOO) is a rare soft tissue sarcoma that produces osteoid and bone. It is sometimes accompanied by cartilage. It is located in soft tissue without skeletal attachment. A previous study revealed that extraosseous osteosarcoma is a chemoresistant tumor with a poor prognosis and should be distinct from osseous osteosarcoma. Out of more than a hundred of osteosarcoma recorded during 1992 to 2012 in Chiang Mai Hospital, only one was EOO. This is a case report of a 44-year-old Asian man who first noticed a small right thigh soft tissue mass associated with pain. MRI reveals a heterogeneous mass in the quadriceps muscle without continuity with the bone. Wide resection of the tumor was performed. Microscopically, the tumors composed of large size spindle shape and bizarre malignant cell with osteoid production. After the resection, adjuvant radiation by brachytherapy technique, and chemotherapy was performed. At postoperative 24-months follow-up, the patient was free from local recurrence and distant metastasis, compared to seven months of median survival time for patients treated with resection alone in previous case reports.